Reconstruction of dorsum of nose after excision of basal cell carcinoma - Dwivedi, Anshuman; Kour, Manmeet; Gupta, Menka (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Basal cell carcinoma, squamous cell carcinoma and melanoma are the most common malignant tumors of the face. The paramedian forehead flap is the standard reconstructive choice for closing large-sized defects of the distal half of the nose. A melolabial interpolation flap and bilobed or trilobed flaps are another option. The dorsal nasal (Rieger) flap is suitable at this location for the closure of small-sized defects, particularly when they are located medially. Here we are discussing an ulcus rodens case we observed in an elderly patient which was treated with a Rieger’s flap.